Properties of pre-germinated rice grain, flour and starch, and use of the flour as texture modifier in crackers - Andiappan, Sarita (2013)
Consumers preferred white or milled rice that has lost most of its nutrients in the milling process. Therefore, an effort in enhancing the nutritional value of the rice through pre-germination which is a natural processing method was studied. The effects of pre-germination on the functional properties of the rice were also studied. Rice of MR 219 and MR 220 varieties were pre-germinated by soaking paddy in water for 24 hours at room temperature, followed by incubation of the soaked paddy on filter paper for 48 hours at 30ºC for growth of embryonic radical up to 0.5 mm. The physical properties of the pre-germinated rice such as grain dimension, color and 1000 kernel weight did not fulfill the specifications of rice grains from varieties MR 219 and MR 220. However, the results indicated that cooking qualities such as cooking time, grain elongation and texture of the pre-germinated rice grains were improved. Less cooking water was required and less solid content was lost during cooking. As the pre-germination process caused a decline in the physical properties of the rice grains, the pre-germinated rice grains were ground into flour and the nutritional and functional properties of the flour was studied. Increased contents of dietary fiber, magnesium, potassium, vitamin B2, vitamin B3, vitamin B6, total phenolics and antioxidants together with medium glycemic index resulted in the pre-germinated rice flour. The carbohydrate, protein, fat and ash contents as well as the functional properties of the rice flour were reduced after pre-germination. In addition, the high yield of pre-germinated rice starch (96%) obtained using water extraction method proposed its utilisation as a value added ingredient in food applications. The amylose content of the pre-germinated rice starch was significantly reduced due to its utilisation for growth of radicle while resistant starch content was increased by 15%. The results also showed that the extracted pre-germinated rice starch gelatinised easily upon heat treatment and formed soft gel that was less viscous. The pre-germinated rice starch was then utilised in the preparation of rice crackers to evaluate its ability to behave as a texture modifier. The hardness, fracturability and crispiness of the rice crackers were improved and were significantly correlated with the proximate composition and starch properties of the pre-germinated rice flour. All the findings were similar for both rice varieties (MR 219 and MR 220). In conclusions, the pre-germination process degraded the physical properties of rice but enhanced the flour and starch properties for the production of softer rice crackers.